Analisis Nilai-nilai Pendidikan Karakter pada Novel Hantu Belang Penunggu Makam Tak Bertuan Karya Erna Erdhiya - Suharti, Sri (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
This study aims to obtain a description of the values ​​of character education in Erna Erdhiya's novel Hantu Belang Penunggu Makam Tak Bertuan. This research is a qualitative research using descriptive method. Data collection techniques in this study consist of; reading carefully and repeatedly, identifying, recording / coding, checking or selecting, and entering data. Data analysis in this study includes interpretation, data analysis, and data conclusion in accordance with the research objectives. The results of this research are the character education values ​​contained in Erna Erdhiya's novel Hantu Belang Penunggu Makam Tak Bertuan are namely religious, honest, discipline, tolerant, creative, curiosity, hard work, love to read, friendly, and responsible.